Impact of multicomponent home-based exercise on fear of falling in older people with a history of falls: insights from the GAITCARE project - Huertas-Hoyas, Elisabet; Neira Álvarez, Marta; Curiel-Regueros, Agustín; Ruiz-Ruiz, Luisa; García-Molina, Rafael; Alonso Bouzón, Cristina; Rincon-Herrera, Eva; García De Villa, Sara; Jiménez-Ruiz, Antonio R. (Frontiers in Aging, 2025)
AimsTo compare the effectiveness of an 8-week multicomponent exercise program delivered at home with digital support versus conventional in-person hospital exercise sessions in reducing FOF.Materials and methodsThe GAITCARE project is a multicenter quasi-experimental trial in three hospitals. Participants were assigned by hospital to either: (1) VIVIFIL App group—individualized daily home exercise with remote supervision; or (2) In person group—face to face exercise at hospital day-care units. The primary outcome was FOF measured by the Short Falls Efficacy Scale–International (Short FES-I). Secondary outcomes included adherence and app satisfaction.Results127 participants were included (64 in App group, 63 in-person group), aged 70–93 (mean 82.36). FOF (SFES-I) was present in 68.3% of the in-person group and 54.7% of the App group. The 8-week intervention reduced FOF scores in both groups, reaching statistical significance only in the in-person group. However, the App group also showed a clinically relevant reduction (∼20%) despite starting with slightly lower baseline FOF, suggesting potential benefits of remote delivery. The in-person group showed higher adherence at weeks 4, 8, and 12 (follow-up). Baseline physical activity influenced adherence, with sedentary participants showing lower adherence. Digital delivery with remote supervision showed good feasibility and was generally well accepted by participants.ConclusionFOF is prevalent in older adults with falls and can be significantly reduced by face-to-face group exercise, which also achieves higher adherence. Enhancements in telematic applications are necessary to improve adherence in digital interventions targeting FOF.